Analisis Kompetensi Sains Biologi dan Kesiapan Karir Mahasiswa - Ibnu Hajar; Maizirwan Mel; Sepita Ferazona; Yeyendra; Johari Afrizal; Farid Agung Prasetio; Jenny Br Simamora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the level of biological competence and career readiness of students in the Biology Education Study Program at Universitas Islam Riau (UIR) in the Academic Year 2024/2025. The research employed a quantitative descriptive method with data collected through questionnaires, interviews, and documentation. The sample consisted of students from the Biology Education Study Program at UIR. A closed-ended questionnaire was designed to measure indicators of biological competence, including conceptual understanding, laboratory skills, critical thinking ability, and the application of biology in real-life contexts. Meanwhile, career readiness was evaluated based on students’ perceptions of their self-potential, career goals, and readiness to enter professional fields such as teaching, research, and biology-based entrepreneurship (bioedupreneur). In-depth interviews were conducted to follow up on the questionnaire results, while academic documentation was used to obtain supporting data related to students’ academic status and learning outcomes. Data were analyzed using univariate statistical analysis. The results show that students possess good biological competence, particularly in conceptual understanding and basic laboratory skills. In addition, students’ career readiness is categorized as high, as indicated by their interest and preparedness to pursue careers as teachers, research assistants, or bioedupreneurs. In conclusion, the implemented curriculum has been able to equip students with knowledge and skills relevant to the demands of the professional world and support their career readiness. Keywords: Bioedupreneur, Biological Competence, Career Readiness